INNOVATION TO PISANG BARLIN (MUSA ACUMINATA AA) AS THE SUBSTITUTE FLOUR (Universitas Negeri Semarang, 2018)
This research is used to explore local ingredients from Musa Acuminata AA. Musa Acuminata AA foodstuffs are usually used only as a raw fruit, not much processed into another food product. Food innovation that raise local potential is needed to increase local food value. This study is an experimentation research, which is uses laboratory experiments at the Food and Beverage Laboratory of Universitas Ciputra Surabaya. Data was collected from 20 respondents by using organoleptic test. There were 3 times of organoleptic test: 1). organoleptic test with whitewash immersion (code 001); 2). organoleptic test with Citroen water immersion (code 002) and 3). organoleptic test without any immersion process (code 003). Musa Acuminata AA flour tested in Research and Industry Standardization Laboratory to know about the moisture, protein, carbohydrate, fiber and potassium. The result: nutrition content code 001. Aw 0.351(25.7C); moisture 7.27%; protein 4.00%; carbohydrate 66.65%; fiber 2.79%; potassium 819.76 mg/100g. Nutrition content for code 002: Aw 0.347(25.6C); moisture 7.30%; protein 4.00%; carbohydrate 68.58%; fiber 2.00%; potassium 780.24 mg/100g. Nutrition content for code 003 Aw 0.536(25.5C); moisture 10.04%; protein 4.01%; Nutrition content for code 68.60%; fiber 1.61%; and potassium 990.18 mg/100g.